Innovations in food packaging - Han, Jung H. (Academic Press, 2013)
This new edition of Innovations in Food Packaging ensures that readers have the most current information on food packaging options, including active packaging, intelligent packaging, edible/biodegradable packaging, nanocomposites and other options for package design. Today's packaging not only contains and protects food, but where possible and appropriate, it can assist in inventory control, consumer education, increased market availability and shelf life, and even in ensuring the safety of the food product. As nanotechnology and other technologies have developed, new and impo.
Includes index.
Keywords: Food -- Packaging.; Food -- Packaging -- Technological innovations.; elektronické knihy; electronic books